ARTIFICIAL INTELLIGENCE IN ENGLISH LANGUAGE TEACHING: OVERCOMING LANGUAGE DIFFICULTIES AND CROSS-LINGUISTIC INTERFERENCE - Muzaffarova Mokhinur Muzaffar kizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This article examines the application of artificial intelligence technologies in English language teaching, with a particular focus on overcoming language difficulties and cross-linguistic interference. The study analyzes key challenges faced by learners, including phonetic, grammatical, and lexical issues that hinder effective language acquisition. Special attention is given to the role of artificial intelligence in personalizing learning processes, providing automated feedback, and enhancing communicative competence. It is concluded that the integration of artificial intelligence into language teaching methodology contributes to increased instructional effectiveness and reduces the impact of cross-linguistic interference.